Rate Of Conditioned Reinforcement Affects Observing Rate But Not Resistance To Change - Shahan, Timothy A (Society for the Experimental Analysis of Behavior, Inc., 2005)
The effects of rate of conditioned reinforcement on the resistance to change of operant behavior have not been examined. In addition, the effects of rate of conditioned reinforcement on the rate of observing have not been adequately examined. In two experiments, a multiple schedule of observing-response procedures was used to examine the effects of rate of conditioned reinforcement on observing rates and resistance to change. In a rich component, observing responses produced a higher frequency of stimuli correlated with alternating periods of random-interval schedule primary reinforcement or extinction. In a lean component, observing responses produced similar schedule-correlated stimuli but at a lower frequency. The rate of primary reinforcement in both components was the same. In Experiment 1, a 4:1 ratio of stimulus production was arranged by the rich and lean components. In Experiment 2, the ratio of stimulus production rates was increased to 6:1. In both experiments, observing rates were higher in the rich component than in the lean component. Disruptions in observing produced by presession feeding, extinction of observing responses, and response-independent food deliveries during intercomponent intervals usually were similar in the rich and lean components. When differences in resistance to change did occur, observing tended to be more resistant to change in the lean component. If resistance to change is accepted as a more appropriate measure of response strength than absolute response rates, then the present results provide no evidence that higher rates of stimuli generally considered to function as conditioned reinforcers engender greater response strength.